Some Econometrics of Growth: Great Ratios of Economics - Klein, L. R.; Kosobud, R. F. (Quarterly Journal of Economics, 1961)
Introduction, 173. — Statistical estimation of the model, 174. — The savings-income ratio, 175. — The capital-output ratio, 178. — Labor's share, 180. — Velocity of circulation, 184. — The capital-labor ratio, 186. — The model as a whole, 188. — Some remarks on the rate of interest, 192. — The aggregate production function and factor substitution, 195. — Another possible great ratio, 197.